ABOUT FORMALIZATION OF COMBINE'S TECHNOLOGICAL ADJUSTMENT'S PROBLEM - V.P. DIMITROV; L.V. BORISOVA (Advanced Engineering Research, 2008)
The axiomatic description of a considered problem is made. Stages of formalization of indistinct expert knowledge are considered.